Effects of resistance exercise (intensity and volume) with or without leucine enriched protein supplementation on human myofibrillar protein synthesis and cell anabolic signalling - Kumar, Vinod (2010)
Sarcopenia or the involuntary age associated muscle wasting starts in the fourth decade of life and accelerates markedly from the fifth decade. This gradual loss of muscle mass eventually results in an inability of older people to carry out simple daily tasks, instability, is associated with an increased risk of falls and fractures, loss of independence, and reduced quality of life. As the number of older people is growing steadily in our society, this in turn places an increasing burden on health care resources, making the topic of sarcopenia and its consequences an important area for research.